Le /r/ de l’anglais dans le corpus IPCE-IPAC : Évaluation quantitative et qualitative des productions orales des apprenants francophones - Ioana Trifu-Dejeu; Nadine Herry-Bénit; Stéphanie Lopez (Anglophonia)
The variability of /r/ in English, and in many other languages of the world, has been widespread and attested for a long time. This variability is all the more likely to prevail among French learners of English. In this study, within the IPCE-IPAC project, we first determine French learners’ rhoticity through an analysis of their realization of /r/ in coda position. We then investigate the quality of /r/ in onset and coda position with an alphanumeric coding system. We aim to establish the extent to which the targeted English accent by the French-speaking learners is complied with, as well as to identify the oral production tasks generating the most errors at the qualitative and quantitative level. A study of the linguistic contexts and of the types of words giving rise to the most errors, will make it possible to identify avenues for remedying the pronunciation of /r/ among French-speaking learners.